A crash course on crises: Macroeconomic concepts for run-ups, collapses, and recoveries - Brunnermeier, Markus K. (Princeton Princeton university press, 2023)
An incisive overview of the macroeconomics of financial crises--essential reading for students and policy experts alikeWith alarming frequency, modern economies go through macro-financial crashes that arise from the financial sector and spread to the broader economy, inflicting deep and prolonged recessions. A Crash Course on Crises brings together the latest cutting-edge economic research to identify the seeds of these crashes, reveal their triggers and consequences, and explain what policymakers can do about them.
Keywords: Macroeconomics; Financial crises; Business and economics